2015
DOI: 10.1097/mbc.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Correction of factor XI deficiency by liver transplantation

Abstract: Orthotopic liver transplantation for other diseases typically results in a coincidental cure for hemophilia A and B; however, long-term outcomes of liver transplant in hemophilia C are not very well described. Herein, the authors report a patient of severe congenital factor XI (FXI) deficiency who received an orthotopic liver transplant. The authors discuss the perioperative management and long-term outcomes. The normalization of his FXI levels confirms that the liver is the most clinically relevant site of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Therapeutic agents available for management of FXI deficiency include FFP, FXI concentrate, antifibrinolytic agents such as ε‐aminocaproic acid or tranexamic acid, desmopressin, and low‐dose activated recombinant factor VII before surgery have been used to prevent bleeding complications 1 . Therapeutic plasma exchange and liver transplantation have also been reported to correct FXI deficiency 10–12 . A systematic review found that the most common treatment for patients with FXI deficiency undergoing surgery or invasive procedures was FXI concentrate (48.4%), followed by FFP (21.6%) 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic agents available for management of FXI deficiency include FFP, FXI concentrate, antifibrinolytic agents such as ε‐aminocaproic acid or tranexamic acid, desmopressin, and low‐dose activated recombinant factor VII before surgery have been used to prevent bleeding complications 1 . Therapeutic plasma exchange and liver transplantation have also been reported to correct FXI deficiency 10–12 . A systematic review found that the most common treatment for patients with FXI deficiency undergoing surgery or invasive procedures was FXI concentrate (48.4%), followed by FFP (21.6%) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Therapeutic plasma exchange and liver transplantation have also been reported to correct FXI deficiency. [10][11][12] A systematic review found that the most common treatment for patients with FXI deficiency undergoing surgery or invasive procedures was FXI concentrate (48.4%), followed by FFP (21.6%). 4 However, the FXI preparations currently available in some European countries were not available in our hospital, and there are concerns about their potential thrombogenicity.…”
Section: Case Presentationmentioning
confidence: 99%
“…Therapeutic plasma exchange has also been reported as a means of avoiding volume overload, which can complicate traditional plasma infusion . The liver appears to be a critical site for FXI production, and FXI deficiency may be corrected by orthotopic liver transplantation …”
Section: Discussionmentioning
confidence: 99%
“…10 The liver appears to be a critical site for FXI production, and FXI deficiency may be corrected by orthotopic liver transplantation. 11,12 Unlike in Hemophilia A and B, routine prophylaxis for everyday activity is not required in individuals with FXI deficiency as they tend not to bleed spontaneously. However, at the time of major surgery or invasive procedures (eg, tonsillectomy, kidney biopsy), prophylaxis must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantace jater byla opakovaně a úspěšně použita i v léčbě jiných vrozených krvácivých stavů -např. u kongenitálního deficitu fibrinogenu, von Willebrandova faktoru, F IX či F XI (11)(12)(13)(14) Z výše uvedených prací vyplývá, že transplantace jater je u pacientů s vrozenou poruchou hemostázy možná a při důsledném vedení a monitoraci substituční terapie i relativně bezpečná, přesto je však ve střednědobém až dlouhodobém horizontu zatížena nezanedbatelnou mortalitou z jiných než hematologických příčin. Na mortalitě pacientů se mimo jiné může podílet i rekurence chronické hepatitidy ve štěpu (1).…”
Section: úVodunclassified